2020
DOI: 10.1111/echo.14941
|View full text |Cite
|
Sign up to set email alerts
|

A review of the pivotal role of cardiac MRI in mitral valve regurgitation

Abstract: Mitral regurgitation (MR) is the most common valvular heart disorder. 1 About 9% of the general population aged more than 75 years in the United States have MR. As the incidence of MR increases with age, the number of patients with MR who require intervention and inpatient care will only increase in the coming decades. 2 MR is divided into two categories: primary organic MR, which occurs as a result of an intrinsically abnormal mitral valve, and secondary or functional MR, which develops secondary to left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(190 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, we can assess SAM and flow acceleration across the LV outflow using the same sequence [ 4 ]. Using three-dimensional volume assessment and phase velocity mapping techniques, we can also assess the mitral regurgitant fraction with precision [ 5 ]. Using gadolinium, we can also assess myocardial fibrosis, which adds prognostic value [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we can assess SAM and flow acceleration across the LV outflow using the same sequence [ 4 ]. Using three-dimensional volume assessment and phase velocity mapping techniques, we can also assess the mitral regurgitant fraction with precision [ 5 ]. Using gadolinium, we can also assess myocardial fibrosis, which adds prognostic value [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…All this information can help guide the management of the patient and can guide the surgeon if septal myectomy is planned. Perhaps, cardiac MRI’s unique attribute is its’ inherent ability to quantitate MR through non-geometric approaches, not reliant on proximal isovolumetric surface area, and to be more accurate than transthoracic or transesophageal echocardiogram, often leading to changes in patient care [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMR offers many advantages in the patient with chronic primary MR. CMR assesses volumetric flows and hence for more accurate, and reproducible measurements of MR severity, particularly when faced with eccentric MR which is often difficult to quantify with conventional echocardiography. Furthermore, CMR is considered the gold standard for the assessments of LV dimensions and LV function and can also provide accurate quantification of LA size and volume [43][44][45][46][47][48][49]. While there is a paucity of high-quality data on CMR based risk-stratification in patients with stage C1 disease, the ACC/AHA Guidelines, provides a Class 1 recommendation for CMR to assess LV and RV volumes and function and MR severity when there is a discrepancy between clinical assessments and echocardiography.…”
Section: Biomarkers: Three-dimensional Echo Echocardiographic Contras...mentioning
confidence: 99%
“…Quantification of mitral regurgitation, and therefore the indication for surgery or percutaneous intervention relies on TTE measurements in the majority of patients [ 1 , 3 ]. In selected cases, however, further investigation, including the use of CMR may be indicated [ 3 , 40 , 60 , 61 ]. CMR studies showed that PCMR reclassified a proportion of patients with mitral regurgitation into a different severity category, which in turn showed better association with prognosis.…”
Section: Introductionmentioning
confidence: 99%